2020
DOI: 10.1101/2020.05.17.100768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ebselen as a highly active inhibitor of PLProCoV2

Abstract: Since December 2019 a novel a coronavirus identified as SARS-CoV-2 or COV2 has been spreading around the world. On the 16th of May around 4.5 million people got infected and over 300,000 died due to the infection of COV2. The effective treatment remains a challenge. Targeted therapeutics are still under investigation. The papain-like protease (PL Pro ) from the human SARS-CoV-2 coronavirus is a cysteine protease that plays a critical role in virus replication. Its activity is required to process the viral poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 26 publications
(34 reference statements)
2
51
0
Order By: Relevance
“…Organoselenium compounds were found to be irresistible inhibitors toward both enzymes. Similar to recently published ebselen [12] they show irreversibility of the mode of action. All of phenylbenzisoselenazol-3(2 H )-ones inactivated completely PL pro Cov2 in concentration equal 20μM (see Table 1).…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…Organoselenium compounds were found to be irresistible inhibitors toward both enzymes. Similar to recently published ebselen [12] they show irreversibility of the mode of action. All of phenylbenzisoselenazol-3(2 H )-ones inactivated completely PL pro Cov2 in concentration equal 20μM (see Table 1).…”
Section: Introductionsupporting
confidence: 88%
“…However, 1d , 1e , 2d and 2e inhibited PL pro CoV2 at this concentration. The investigation of IC 50 revealed that 1d , 1e , 2d and 2e obtained approximately 250 nM that is one magnitude better than in the case of ebselen (around 2 μ M as reported in [12]).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations